DESIGN OPTIMIZATION AND ANALYSIS OF VERTICAL AXIS WIND TURBINE BLADE - Jarral, A.; Ali, M.; Sahir, M. H.; Pasha, R. A. (The Nucleus, 2013)
Wind Energy is clean and renewable source of energy and is also the world’s fastest growing energy resource. Keeping in view power shortages and growing cost of energy, the low cost wind energy has become a primary solution. It is imperative that economies and individuals begin to conserve energy and focus on the production of energy from renewable sources. Present study describes a wind turbine blade designed with enhanced aerodynamic properties. Vertical axis turbine is chosen because of its easy installment, less noisy and having environmental friendly characteristics. Vertical axis wind turbines are thought to be ideal for installations where wind conditions are not consistent. The presented turbine blade is best suitable for roadsides where the rated speed due to vehicles is most often 8 ms-1 .To get an optimal shape design symmetrical profile NACA0025 has been considered which is then analyzed for stability and aerodynamic characteristics at optimal conditions using analysis tools ANSYS and CFD tools.